Structural mpdel of chronic pain based on mindfulness, social support and life events with the mediating role of pain catastrophizing - susan Bahrami Koohshahi; Fatemeh Golshani; Anita Baghdassarians; Afsaneh Ghanbari Panah (مجله علوم روانشناختی)
Background: Emotional and cognitive states directly affect the neural mechanisms of chronic pain, And increasing pain negatively affects the emotional and cognitive states of a person. Despite the growing research evidence of the effects of psychological variables such as mindfulness, social support, stress and pain catastrophizing on the phenomenon of chronic pain, the general effects of these variables have been less investigated in the form of comprehensive causal model. Aims: The present study was conducted with the aim of investigating the structural model of chronic pain based on mindfulness, social support and life events with the Mediating of pain catastrophizing. Methods: The method of the present study was descriptive-correlation type of structural equation modeling. The statistical population of the study included all male and female patients with chronic pain who were treated for follow-up treatment in 2022, they had referred to pain clinics, pain specialists, neurologists, physiotherapists, and health centers in Tehran with problems related to musculoskeletal pain and rheumatoid arthritis, of which 496 people were selected using the available sampling method. Data collection tools include the Mc Gill Pain Questionnaire (Melzack, 1975), the Five Factor Mindfulness Questionnaire (Baer et al., 2006), the Multidimensional Scale of Perceived Social Support by Zimet et al. (1988), Scale of Life stressful Events‐Paykel (Paykel et al., 1971) and Pain Catastrophizing Scale (Sullivan et al., 1995). Data analysis was done by structural equation modeling method and using SPSS-23 and AMOS-23 software. Results: The results of modeling of structural equations indicated a good fit of the model with experimental data. The effect of the coefficient of the direct standard path of mindfulness on the experience of chronic pain was significant and the indirect path of mindfulness on the experience of chronic pain with the mediating role of pain catastrophizing was significant (P< 0.05). The effect of direct and indirect standard path coefficient of social support with mediating role of pain catastrophizing on chronic pain experience was not significant (P> 0.05). The direct and indirect path of the number of stressful factors on the experience of chronic pain was also insignificant (P> 0.05). However, the standard direct and indirect path of the amount of stressful factors on the experience of chronic pain with the mediating role of catastrophizing was also significant (P< 0.05). Conclusion: According to the obtained results, it seems that mindfulness, social support and life events play an important role in explaining chronic pain by mediating pain catastrophizing. Considering that these variables have a significant contribution in predicting the pain of chronic pain patients, Therefore, mental health professionals can use these factors to improve the mental health of people with chronic pain.